2000
DOI: 10.1191/095968300669405262
|View full text |Cite
|
Sign up to set email alerts
|

AMS 14C dating of Holocene estuarine deposits: consequences of high-energy and reworked foraminifera

Abstract: Benthic foraminiferal species were used to AMS date Holocene sediments adjacent to transgressive overlap boundaries (TOB) in two high energy estuaries in North Spain. It had previously been recognised that the foraminifera could be divided into indigenous and exotic components. Whereas it was known that the exotic forms had been transported into the estuaries from the adjacent inner shelf, it was assumed that the indigenous forms were in situ. The AMS dates based on indigenous forms obtained from pairs of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…The distribution of modern microfaunas in the Basque salt marshes has been studied previously by Leorri et al (2008b) who demonstrated the presence of well defined assemblages that occupy clear elevation subenvironments related to degree or duration of exposure to tidal inundation. Furthermore, microfaunas (both agglutinated and calcareous) are well preserved and abundant in the subsurface sediments due to supply of abundant calcium carbonate to the environment by regional rocks (Cearreta and Murray, 2000). This good preservation of the complete modern assemblages (calcareous component included) is of great advantage in the paleoenvironmental interpretation of buried sequences.…”
Section: Interpretation Of the Sedimentary Recordmentioning
confidence: 99%
“…The distribution of modern microfaunas in the Basque salt marshes has been studied previously by Leorri et al (2008b) who demonstrated the presence of well defined assemblages that occupy clear elevation subenvironments related to degree or duration of exposure to tidal inundation. Furthermore, microfaunas (both agglutinated and calcareous) are well preserved and abundant in the subsurface sediments due to supply of abundant calcium carbonate to the environment by regional rocks (Cearreta and Murray, 2000). This good preservation of the complete modern assemblages (calcareous component included) is of great advantage in the paleoenvironmental interpretation of buried sequences.…”
Section: Interpretation Of the Sedimentary Recordmentioning
confidence: 99%
“…Cearreta and Murray (1996) describe a TOB surface in the ria of Santoña, in the context of a stepped rising of the sea-level in this area. Nevertheless the dating of this TOB was not possible with foraminifers due to the bad preservation of the tests (Cearreta and Murray, 2000). In the Bidasoa estuary Cearreta (1994) 7810 ± 130 BP, indicating the age where the estuary was established in the area.…”
Section: Relative Sea-level Changesmentioning
confidence: 99%
“…Age estimates were calibrated using CALIB 5.0.1 (Stuiver et al, 2005) and reported as radiocarbon calibrated years before present (present ¼ 1950 CE). The dates obtained on shell material were also corrected for the marine reservoir effect (apparent surface-water age), which has been estimated to be around 400 years on the Bay of Biscay (Cearreta and Murray, 2000).…”
Section: Geochemical Analysesmentioning
confidence: 99%
“…Previous studies in northern Spain have shown that foraminifera correlate to elevation with respect to mean tidal level (Cearreta and Murray, 1996;Leorri and Cearreta, 2004;Leorri et al, 2008b). To date, only regional transfer functions have been carried out in the Basque coast (Leorri et al, 2008a(Leorri et al, ,b, 2010 and used for the reconstruction of sea level in different salt marshes from this region (Leorri et al, 2008b;Leorri and Cearreta, 2009b).…”
Section: Introductionmentioning
confidence: 97%